PENERAPAN DATA MINING UNTUK ANALISIS POLA BELANJA KONSUMEN MENGGUNAKAN ALGORITMA APRIORI PADA MALL CPM JAKARTA - Persis Haryo Winasis (Jurnal Sistem Informasi dan Informatika (Simika), 2019)
Companies engaged in retail such as malls that have a lot of transaction data and sales transactions that are very much. Every purchase transaction made by consumers will be recorded and purchased in one database. Processing data in this study was carried out using a priori algorithm and using the help of the Weka application. The results of data mining in this study are expected to be able to produce new information about spending patterns in a certain period that can be used by the mall manager and store manager to support each related product promotion or organizing an event to increase the number of consumers in a certain period.